Labor Representation in Governance as an Insurance Mechanism - Kim, E Han; Maug, Ernst; Schneider, Christoph (Review of Finance, 2018)
We hypothesize that labor participation in governance helps improve risk sharing between employees and employers. It provides an ex post mechanism to enforce implicit insurance contracts protecting employees against adverse shocks. Results based on German establishment-level data show that skilled employees of firms with 50% labor representation on boards are protected against layoffs during adverse industry shocks. They pay an insurance premium of 3.3% in the form of lower wages. Unskilled blue-collar workers are unprotected against shocks. Our evidence suggests that workers capture all the gains from improved risk sharing, whereas shareholders are no better or worse off than without codetermination.